Development of Learning Video Media in Biology Subjects - Asia, Nur; Kinda, Johanis; Edwards, Joseph (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
The purpose of this study is to produce valid and practical learning video media for use in the learning process. This research is a development research used to produce a product in the form of learning video media. The stages in this development include: planning stage, design stage, and development stage. The subjects in this study were 2 validators consisting of learning media experts and content or learning media material experts, 31 grade XI science students and 1 Biology subject teacher. Data collection techniques used observation, interviews, questionnaires and documentation. The data analysis techniques used were Qualitative Descriptive Analysis, and Descriptive Static Analysis. Research on this offers novelty in the form of more visual and interactive learning media, allowing students to understand complex biological concepts through interesting graphical and animated representations. In addition, these learning videos provide flexibility for students to learn independently and repeatedly, thus improving conceptual understanding and accommodating various learning styles.